2016
DOI: 10.1016/j.agwat.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neural network modeling to predict non-water-stressed leaf temperature in wine grape for calculation of crop water stress index

Abstract: a b s t r a c tPrecision irrigation management of wine grape requires a reliable method to easily quantify and monitor vine water status to allow effective manipulation of plant water stress in response to water demand, cultivar management and producer objective. Mild to moderate water stress is desirable in wine grape in determined phenological periods for controlling vine vigor and optimizing fruit yield and quality according to producer preferences and objectives. The traditional leaf temperature based crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 42 publications
(66 reference statements)
0
44
0
Order By: Relevance
“…In more stressful conditions (37 • C and very low air humidity), the authors measured a difference of 13 • C in 'Syrah' and 17 • C in 'Malbec' (T nws − T air ). King and Shellie [163] report that a difference between canopy and air temperature of vines of about 17 • C, which is much higher than with T dry values assumed in other studies and slightly less than the energy balance models developed by Jones [111]. T dry for calculation of the CWSI was estimated as T air + 15 • C for both grape cultivars, resulting in a CWSI value between 0 and 1 for irrigation scheduling purposes.…”
Section: Sunlit and Shade Leavesmentioning
confidence: 99%
See 4 more Smart Citations
“…In more stressful conditions (37 • C and very low air humidity), the authors measured a difference of 13 • C in 'Syrah' and 17 • C in 'Malbec' (T nws − T air ). King and Shellie [163] report that a difference between canopy and air temperature of vines of about 17 • C, which is much higher than with T dry values assumed in other studies and slightly less than the energy balance models developed by Jones [111]. T dry for calculation of the CWSI was estimated as T air + 15 • C for both grape cultivars, resulting in a CWSI value between 0 and 1 for irrigation scheduling purposes.…”
Section: Sunlit and Shade Leavesmentioning
confidence: 99%
“…Stated below King and Shellie [163] obtained CWSI values ranging from 0 to 1, when adopting the T air + 5 • C for estimating the temperature of non-transpiring leaves (T dry ), as proposed by Irmak et al [201] and Möller et al [108] for corn and grape, respectively. The authors found that the maximum temperature difference between the canopy of deficit-irrigated vines and T air was influenced by irrigation frequency.…”
Section: Sunlit and Shade Leavesmentioning
confidence: 99%
See 3 more Smart Citations